The state and society : Peru in comparative perspective - Stepan, Alfred C. (Princeton legacy library., 1978)
Although the state's role in society has clearly expanded since the 1930s, its independent effect on social structure and change has been given little weight in modern political theories. To bring theory more into line with reality, Stepan proposes a new model of state autonomy which he shows to be particularly well suited for understanding political developments in the Iberian countries and their former Latin-American colonies. Originally published in 1978. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.